Innate Lymphoid Cells Are Required to Induce Airway Hyperreactivity in a Murine Neutrophilic Asthma Model - Jonckheere, Anne-Charlotte; Seys, Sven F.; Steelant, Brecht; Decaesteker, Tatjana; Dekoster, Kaat; Cremer, Jonathan; Dilissen, Ellen; Schols, Dominique; Iwakura, Yoichiro; Vande Velde, Greetje; Breynaert, Christine; Schrijvers, Rik; et al. (Frontiers in Immunology, 2022)
Rationale: Non-allergic asthma is driven by multiple endotypes of which neutrophilic and pauci-granulocytic asthma have been best established. However, it is still puzzling what drives inflammation and airway hyperreactivity (AHR) in these patients and how it can be treated effectively. Recently a potential role of the innate immune system and especially the innate lymphoid cells (ILC) has been proposed. Objective: In this study, we investigated effects of LPS inhalation on airway inflammation and AHR as potential model for elucidating the pathogenesis of non-allergic asthma. Methods: Wild type (BALB/c), SCID, IL-17A-/- and Rag2-/- 𝛾C-/- mice were endonasally exposed to lipopolysaccharide (LPS, 2µg) on four consecutive days. Twenty-four hours after the last exposure, AHR to methacholine was assessed. Cytokine levels and ILC subpopulations were determined in lung tissue. Cellular differential analysis was performed in BAL fluid. Main Results: In this study, we developed a murine model for non-allergic neutrophilic asthma. We found that repeated endonasal applications of low dose LPS in BALB/c mice led to AHR, BAL neutrophilia and a significant increase in lung ILC3 as well as a significant increase in lung chemokines KC, MIP-2 and cytokines IL-1β, IL-17A, IL-22 and TNF. Adoptive transfer of ILC in Rag2-/- 𝛾C-/- mice showed that ILC played a causal role in the induction of AHR in this model. Antagonising IL-1β, but not IL-17A or neutrophils, resulted in a partial reduction in LPS-induced AHR. Conclusion: In conclusion, we report here a murine model for neutrophilic asthma where ILC are required to induce airway hyperreactivity.